2014
DOI: 10.1073/pnas.1407837111
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for a mirror-image conformation as a subtle effect in protein folding

Abstract: By using local (free-energy profiles along the amino acid sequence and 13 C α chemical shifts) and global (principal component) analyses to examine the molecular dynamics of protein-folding trajectories, generated with the coarse-grained united-residue force field, for the B domain of staphylococcal protein A, we are able to (i) provide the main reason for formation of the mirror-image conformation of this protein, namely, a slow formation of the second loop and part of the third helix (Asp29-Asn35), caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…It is essential for them to selectively fold into functional and unique 3D structures because their misfoldings can lead to the malfunctioning of the proteins and cause various disorders such as Alzheimer's, and Parkinson's diseases. 1,2 Understanding the protein folding within biological membrane is therefore the key to unlocking their ability to manipulate biological systems and potential role in treating diseases. [3][4][5] Despite the importance of membrane protein folding, a molecular level understanding of the folding mechanisms is generally much less comprehensive than that for the water-soluble proteins.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential for them to selectively fold into functional and unique 3D structures because their misfoldings can lead to the malfunctioning of the proteins and cause various disorders such as Alzheimer's, and Parkinson's diseases. 1,2 Understanding the protein folding within biological membrane is therefore the key to unlocking their ability to manipulate biological systems and potential role in treating diseases. [3][4][5] Despite the importance of membrane protein folding, a molecular level understanding of the folding mechanisms is generally much less comprehensive than that for the water-soluble proteins.…”
Section: Introductionmentioning
confidence: 99%
“…12). The fourth one led to a mirror-image conformation, the reason for which has now been proposed (Kachlishvili et al 2014). It was shown that the formation of the mirror-image conformation (see Fig.…”
Section: Protein Folding With Eceppmentioning
confidence: 91%
“…This protein has been the subject of extensive theoretical (Olszewski, Kolinski & Skolnick, 1996;Vila, Ripoll & Scheraga, 2003;Garcia & Onuchic, 2003;Lee et al, 2006;Kachlishvili et al, 2014) and experimental (Deisenhofer, 1981;Gouda et al, 1992;Bai et al, 1997;Myers & Oas, 2001;Sato et al, 2004;Dimitriadis et al, 2004;Noel et al, 2012) studies because of its biological importance and small size. In contrast to this, the mirror-image conformation has been subject of limited discussion (Olszewski, Kolinski & Skolnick, 1996;Vila, Ripoll & Scheraga, 2003;Garcia & Onuchic, 2003;Noel et al, 2012;Kachlishvili et al, 2014). The reason for this might be that the mirror image conformation of this protein has been observed only in some theoretical studies with different force fields but it has never been detected experimentally.…”
Section: Introductionmentioning
confidence: 99%